Music Recommendation System Using Association Rule Mining and Clustering Technique To Address Coldstart Problem (International Journal of Engineering and Computer Science, 2014)
Recommender system based on data mining is very useful, more accurate and provides worldwide services to the user. Recommender systems are becoming very popular in recent years. More and more people rely on online sites for purchasing songs, apparels, books, rented movies etc. The competition between the online sites forced the web site owners to provide personalized services to their customers. So the recommender systems came into existence. Recommender systems are active information filtering systems that attempt to present to the user, information items in which the user is interested in. The recommender systems also suffer from issues like cold start, sparsity. Cold start problem is that the recommenders cannot draw inferences for users or items for which it does not have sufficient information. This paper attempts to propose a solution to the cold start problem by combining association rules and clustering technique.